2021
DOI: 10.1101/2021.11.11.21266048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning Based Prediction of COVID-19 Mortality Suggests Repositioning of Anticancer Drug for Treating Severe Cases

Abstract: Despite available vaccinations COVID-19 case numbers around the world are still growing, and effective medications against severe cases are lacking. In this work, we developed a machine learning model which predicts mortality for COVID-19 patients using data from the multi-center ‘Lean European Open Survey on SARS-CoV-2-infected patients’ (LEOSS) observational study (>100 active sites in Europe, primarily in Germany), resulting into an AUC of almost 80%. We showed that molecular mechanisms related to dement… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The results suggested that non-invasive features could provide mortality predictions that are similar to the invasive. The next study [10] experimentally verified that some anti-cancer drugs can be regarded as potential treatments against COVID-19. A broad panel of time-to-event machine learning models was implemented and compared, such as Elastic net penalized Cox proportional hazards regression and Weibull accelerated failure time regression, DeepSurv neural network approach, Random Survival Forests and XGBoost Survival Embeddings.…”
Section: Related Workmentioning
confidence: 75%
“…The results suggested that non-invasive features could provide mortality predictions that are similar to the invasive. The next study [10] experimentally verified that some anti-cancer drugs can be regarded as potential treatments against COVID-19. A broad panel of time-to-event machine learning models was implemented and compared, such as Elastic net penalized Cox proportional hazards regression and Weibull accelerated failure time regression, DeepSurv neural network approach, Random Survival Forests and XGBoost Survival Embeddings.…”
Section: Related Workmentioning
confidence: 75%